2010
DOI: 10.2147/opth.s9608
|View full text |Cite
|
Sign up to set email alerts
|

Acrylic toric intraocular lens implantation: a single center experience concerning clinical outcomes and postoperative rotation

Abstract: Purpose: To present clinical results of toric intraocular lens (IOL) implantation for preexisting astigmatism correction and determine the time of any postoperative rotation. Patients and methods: Twenty-nine eyes of 19 patients underwent uncomplicated phacoemulsification and were implanted with an Acrysof © toric IOL. Uncorrected visual acuity, residual astigmatism, and postoperative rotation of the IOL were estimated one and six months after the operation. Results: Uncorrected visual acuity was 0.5 in 26 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…Becker et al 19 measured the in-the-bag stability of a hydrophilic acrylic IOL and reported an average IOL rotation of 5.3±1.4° after 6 months compared to the position directly after implantation. Another study by Tsinopoulos et al 20 evaluated the rotational stability after in-the-bag implantation of Acrysof toric lenses (Alcon, Fort Worth, TX, USA) and found a mean IOL axis rotation of 2.7±1.5° with a range from 0.9 to 8.4°. Comparable outcomes were reported by Draschl et al 21 in J o u r n a l P r e -p r o o f 2017.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Becker et al 19 measured the in-the-bag stability of a hydrophilic acrylic IOL and reported an average IOL rotation of 5.3±1.4° after 6 months compared to the position directly after implantation. Another study by Tsinopoulos et al 20 evaluated the rotational stability after in-the-bag implantation of Acrysof toric lenses (Alcon, Fort Worth, TX, USA) and found a mean IOL axis rotation of 2.7±1.5° with a range from 0.9 to 8.4°. Comparable outcomes were reported by Draschl et al 21 in J o u r n a l P r e -p r o o f 2017.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Por una parte se han empleado en diferentes estudios que modelizan la AV en función del error refractivo astigmático para diferentes orientaciones del eje (Guo, 2010;Atchison, 2011;Ohlendorf, 2011). Por otra parte, tal y como se mencionó antes, los resultados se han utilizado recientemente en cirugía de cataratas para valorar el efecto de la incisión realizada para compensar el astigmatismo preoperatorio en la AV final (Cho, 2009) y la rotación del eje del cilindro de una LIO tórica en la AV postoperatoria (Tsinopoulos et al 2010). En ambos estudios se concluye que la AV final no se ve afectada por el eje del astigmatismo.…”
Section: Lentes Intraoculares Multifocales Evaluadas Y Protocolo De M...unclassified